Academic identity in a performative and marketised environment: a comparative case study - Pearson, Robert William (2015)
This thesis reports a study of academic identity in two English universities of different type and status during the period 2012 to 2013. It explores the effects on academic identity of policy developments which have reconfigured the relationship between academics, students and government since the late 1970s. These developments have resulted in a change to the university working environment from one in which academics enjoyed relative autonomy in their academic practice, to one in which work is increasingly directed by externally imposed performative and marketised priorities. The most recent policy developments were introduced by the 2010 UK Conservative Liberal Democrat Coalition Government and included major changes to the funding of university education in England. This has resulted in the withdrawal of government funding for non-laboratory based disciplines, the tripling of tuition fees to £9,000 per annum, and the transferal of the burden of funding from the state to students.